Functional interaction between p90(Rsk2) and Emi1 contributes to the metaphase arrest of mouse oocytes - Paronetto, Maria Paola (Nature Publishing Group, 2004)
Vertebrate eggs arrest at metaphase of the second meiotic division before fertilization under the effect of a cytostatic factor (CSF). This arrest is established during oocyte maturation by the MAPK kinase module, comprised of Mos, MEK, MAPKs and p90(Rsk). Maintenance of CSF arrest at metaphase requires inhibitors of the anaphase-promoting complex (APC) like Emi1, which sequesters the APC activator Cdc20. Although it was proposed that the Mos pathway and Emi1 act independently, neither one alone is sufficient to entirely reproduce CSF arrest. Herein we demonstrate that p90(Rsk2) associates with and phosphorylates Emi1 upstream of the binding region for Cdc20, thus stabilizing their interaction. Experiments in transfected cells and two-cell embryos indicate that Emi1 and p90(Rsk2) cooperate to induce the metaphase arrest. Moreover, oocyte maturation was impaired by interfering with the interaction between p90(Rsk2) and Emi1 or by RNA interference of Emi1. Our results indicate that p90(Rsk2) and Emi1 functionally interact during oocyte maturation and that the Mos pathway establishes CSF activity through stabilization of an APC-inhibitory complex composed by Emi1 and Cdc20 before fertilization.